A previously uncharacterized gene, PA2146, contributes to biofilm formation and drug tolerance across the ɣ-Proteobacteria - Matthew F. Kaleta; Olga E. Petrova; Claudia Zampaloni; Fernando Garcia-Alcalde; Matthew Parker; Karin Sauer (npj Biofilms and Microbiomes, 2022)
Abstract Transcriptomic studies have revealed a large number of uncharacterized genes that are differentially expressed in biofilms, which may be important in regulating biofilm phenotypes such as resistance to antimicrobial agents. To identify biofilm genes of unknown function in P. aeruginosa, we made use of RNA-seq and selected 27 uncharacterized genes that were induced upon biofilm growth. Biofilms by respective mutants were subsequently analyzed for two biofilm characteristics, the biofilm architecture and drug susceptibility. The screen revealed 12 out of 27 genes to contribute to biofilm formation and 13 drug susceptibility, with 8 genes affecting both biofilm phenotypes. Amongst the genes affecting both biofilm phenotypes was PA2146, encoding a small hypothetical protein that exhibited some of the most substantial increases in transcript abundance during biofilm growth by P. aeruginosa PAO1 and clinical isolates. PA2146 is highly conserved in ɣ-proteobacteria. Inactivation of PA2146 affected both biofilm phenotypes in P. aeruginosa PAO1, with inactivation of homologs in Klebsiella pneumoniae and Escherichia coli having similar effects. Heterologous expression of PA2146 homologs complemented the P. aeruginosa ∆PA2146, suggesting that PA2146 homologs substitute for and play a similar role as PA2146 in P. aeruginosa.